The TTIP : the Transatlantic Trade and Investment Partnership between the European Union and the United States - Babarinde, Olufemi; Domínguez, Roberto; Roy, Joaquín 1943-; Lecea y Flores de Lemus, Antonio de; Moulioukova, Dina; University of Miami. Jean Monnet Chair (Jean Monnet Chair, University of Miami, 2014)
This volume studies the plan of the TTIP in depth and points out the impact on other regions of the world. It also discusses similar alliances made by the two partners.